SLC20A1 Is Involved in Urinary Tract and Urorectal Development - Rieke, Johanna Magdalena; Zhang, Rong; Braun, Doreen; Yilmaz, Öznur; Japp, Anna S.; Lopes, Filipa M.; Pleschka, Michael; Hilger, Alina C.; Schneider, Sophia; Newman, William G.; Beaman, Glenda M.; Nordenskjöld, Agneta; et al. (Frontiers in Cell and Developmental Biology, 2020)
Previous studies in xenopus and zebrafish (zf) provide a detailed description of the embryonic role of the phosphate transporter slc20a1a in early pronephric kidney formation. The recent identification of SLC20A1 as a monoallelic candidate gene for cloacal exstrophy further suggests its involvement in lower urinary tract and urorectal development. However, the knowledge about the role of SLC20A1 in the embryonic formation of the lower urinary tract is poor. To broaden our understanding of the embryonic impact of SLC20A1 in urinary tract and urorectal development in the zebrafish we induced morpholino oligonucleotide (MO) knockdown of the zebrafish orthologue slc20a1a. This caused kidney cysts and malformations of the cloaca. Moreover, in morphants we demonstrated dysfunctional voiding and hindgut opening defects mimicking imperforate anus in human cloacal exstrophy. Furthermore, we performed immunohistochemistry of an unaffected six-week-old human embryo and detected SLC20A1 in most locations of the urinary tract and in the abdominal midline, consistent with relevant anatomical structures involved in the pathogenesis of cloacal exstrophy. Additionally, we re-sequenced SLC20A1 in 690 individuals with bladder exstrophy-epispadias complex (BEEC) including 84 individuals with cloacal exstrophy. We identified two additional monoallelic de novo variants. One was identified in a case-parent trio with classic bladder exstrophy and one additional novel de novo variant in an affected mother who transmitted this variant to her affected son. To study the functional impact of the identified SLC20A1 variants we expressed them in HEK293 cells. Our findings suggest that phosphate transport is not involved in the disease mechanism. Yet, we found lower expression levels of cleaved caspase-3, reflecting an implication of SLC20A1 in apoptosis pathways. Our results suggest SLC20A1 to be involved in urinary tract and urorectal development and implicate SLC20A1 as a disease-gene for human bladder exstrophy-epispadias complex (BEEC).